Analysis of Soil Chemical Properties as Indicators of Soil Fertility in Agricultural Land in Taniwel Village, West Seram Regency - Sovian Sesca Elly; Sintje Liline (Jurnal Geografi, Lingkungan dan Kesehatan, 2026)
This study was conducted to analyze soil nutrient content as an indicator of soil fertility in agricultural land. The research focused on evaluating soil nutrient parameters, including nitrogen (N), phosphorus (P), potassium (K), organic carbon (C-organic), organic matter, and soil pH. The findings are expected to provide an overview of the soil condition in Taniwel Village and serve as a basis for more effective and sustainable agricultural land management in the area. This study employed a qualitative descriptive method with an experimental approach through direct laboratory analysis of soil samples. Data were collected by analyzing soil nutrient content, organic carbon, organic matter, and soil pH. Laboratory analyses were carried out using the electrometric method for pH (H₂O and 1N KCl), the Walkley and Black method for organic carbon and organic matter, the Kjeldahl method for total nitrogen, the Bray-1 method for available phosphorus, and the NH₄OAc extraction method at pH 7 for available potassium. The laboratory analysis revealed that the soil contained 0.34% total nitrogen, 5.99 ppm available phosphorus, 0.30 cmol (+)/kg available potassium, 3.51% organic carbon, 6.08% organic matter, a soil pH (H₂O) of 5.5, and a soil pH (1N KCl) of 5.2. These findings indicate that the agricultural soils in Taniwel Village possess fertility characteristics that are generally favorable for plant growth.